Mitigating the oxidative stress caused by UV-B in date palm seedlings: efficacy of salicylic acid and ascorbic acid application - Swaid Sajeda Yaseen; Shareef Hussein Jasim (Folia Oecologica, 2025)
The date palm is one of the plants whose growth is being affected by global warming through harmful wavelengths of UV radiation. The protective role of salicylic acid (SA) and ascorbic acid (AsA) at physiological (100 and 200 mg l–1) levels was assessed under UV-B (8 hrs day–1) stress in the development and physiological adaptation of date palm seedlings. Three months after treatment with different concentrations of SA and AsA, their effects on growth criteria, pigment content, oxidation stress markers, and enzyme antioxidant activities were studied. Results revealed that both SA and AsA increased the seedling height, leaf width, and dry weight, decreased the level of malondialdehyde and hydrogen peroxide, and increased membrane stability, thereby alleviating oxidant injury. Furthermore, activities of antioxidant enzymes such as peroxidase and ascorbate peroxidase have been upregulated, thereby enhancing the seedlings’ tolerance against stress. The results suggest that foliar SA and AsA application could be an efficient way to alleviate the UV-B radiation stress damage in young date palm plants, therefore providing a possible approach to improving crop resilience in increasingly harsh environmental conditions.